PENERAPAN TEKNIK SKETSA DENGAN KERTAS KARBON, MENINGKATKAN HASIL BELAJAR SENI LUKIS REALIS , SISWA KELAS XI SMK NEGERI 1 SUKAWATI TAHUN PELAJARAN 2021/2022 - Juliarta, I Putu Bambang (Institut Seni Indoensia Surakarta, 2022)
Realist painting is one of the competencies that must be mastered to determine students' ability to paint with oil paints. Potential students who have talents and interests become the right place for each student's for self-development. Development of technology, social culture and the world of business, industry and work (DUDIKA), make an update on the curriculum. Learning conditions during the Covid-19 period which were carried out online learning required students to study independently. Differences in the abilities of students who have talents and interests require guidance during the pandemic. Preliminary observation, the percentage of completeness level of each student realist painting learning outcomes with avarge value of 40%, that makes researchers interested to research on Class. This research method is a classroom action research. The subject of this research were class XI SMK Negeri 1 Sukawati Student in the even semester 2020/2021 with the 30 people. Collecting data technique using primary data from the outcome learning assessment student and secondary data by field observation. Data analysis method with qualitative descriptive analysis method.The results of this research that The Application of Sketching Techniques with Carbon Paper, Improves Realist Painting Learning Outcomes for Class XI Students of SMK Negeri 1 Sukawati in the 2021/2022 Academic Year. This result can be seen from observation data of outcome learning assessment in the first cycle is average value of 79 and increasing to average value of 85 in the second cycle, percentage of completeness 77%, and increasing in second cycle with average value of 87% and 26 students declared completed.